Oral Health Knowledge, Attitude, and Behavior Among Health Professions’ Students at Kabul University of Medical Sciences [Response to Letter] - Ehsan H; Ahmadzai N; Orfani Z; Rezayee BM; Wally M; Daftani S (Dove Medical Press, 2024)
Hedayatullah Ehsan,1,2 Nazera Ahmadzai,3 Zarlasht Orfani,2 Bibi Marwa Rezayee,2 Moqadasa Wally,2 Sardara Daftani2 1Medical Sciences Research Center, Ghalib University, Kabul, Afghanistan; 2School of Stomatology, Kabul University of Medical Sciences, Kabul, Afghanistan; 3Department of Pediatric Dentistry, Kabul University of Medical Sciences, Kabul, AfghanistanCorrespondence: Hedayatullah Ehsan, Email hedayatullahehsan@gmail.com